Delayed enzymatic debridement in severe burns: Proof of concept. Issue 4 (October 2021) - Waldner, M.; Zucal, I.; Gentzsch, T.; Klein, H.J.; Schweizer, R.; Kim, B.S.; Bühler, K.P.; Giovanoli, P.; Plock, J.A.
Highlights: Enzymatic debridement in burns has evolved as an alternative to surgical debridement. Delayed enzymatic debridement is feasible with similar results for wound healing. Delayed enzymatic debridement may come along with higher wound infection rates. Abstract: Introduction: Enzymatic debridement (ED) is a novel powerful therapy for debridement of severe burns. Standard ED is usually performed within 72 h after injury following a presoaking phase. Little evidence exists on the effectiveness of ED later than 72 h after trauma. In this retrospective study, we compared outcomes of burn patients treated within versus later than 72 h after injury. Patients and Methods: 110 patients with severe burns treated with ED between 2016 and 2020 were evaluated. Patients treated later than 72 h after trauma were identified and matched to a control group treated within 72 h. Matching criteria included age, area treated with ED, and localization of ED. Exclusion criteria were abbreviated burn severity index (ABSI) greater than 12 and death within the first 10 days after burn injury. Primary outcomes were time to full epithelialization and number of secondary surgical interventions. Results: 16 patients (11 female, 5 male) matched the inclusion criteria and were assigned to the late treatment group. Mean age was 54.0 ± 19.0 years, the = and mean ABSI score 6.3 ± 3.2. 16 matched patients were assigned to the early ED group. Secondary surgical procedures were performed in 62.5% of cases in both groups with a mean of 1.7 (late treatment) vs. 2.2 (control; p = 0.29) secondary procedures in each group, respectively. No significant difference between groups regarding time to complete epithelialization (28.2 days vs. 27.3 days, p = 0.45) was observed. Infection rate was higher (18.8% vs. 6.3%, p = 0.28) in the delayed group. Conclusion: Delayed ED is a feasible procedure as part of personalized care in burn surgery. In our retrospective study, we could not identify r safety issues except a slightly higher infection rate. This may however be attributed to delayed initiation of burn treatment itself.